Familiarity and perception of perceived use of artificial intelligence on social media marketing posts - Angeles, Kate F. Camano, Ivy B. Dela Cruz, Cheska Mica M. Lucena, Lhoreen D. Puso, Louise Sebastian G. Ramos, Harem Dyana G. Regalario, Jette Dianne F. Salud, Jessica Fritz D. 4 0 16; 5
ABSTRACT The research investigated how awareness of Al-generated visuals influences Gen Z consumers' trust and authenticity perceptions toward brands. This is based on the foundation of the Digital Natives Theory that those who grew up in the digital age have differing perceptions on technologies than those who didn't. A descriptive online survey with Likert-scale questions was administered to 151 Generation Z consumers in Manila City familiar with Al image generation in brand posts. The findings revealed a high awareness of Al-generated images among Gen 2 consumers, with an increasing perception of their use in social media marketing. While skepticism towards manipulated Al-generated images exists, transparency about Al usage significantly improves brand trust. Consumers express greater acceptance of Al-generated content when it aligns with brand identity, messaging, and values. They also prefer combining Al-generated and real images for a more authentic brand experience. Interestingly, the study found a weak overall influence of perceived Al use on brand perception, suggesting that factors beyond mere awareness of Al play a more significant role. The results revealed the need for a more comprehensive study, focusing on proper disclosure of usage and authenticity to further understand Gen Z's attitudes and behaviors toward Al-generated content in social media marketing. This study provided valuable insights for brands targeting Gen Z consumers and contributes to the ongoing academic discourse on the intersection of Al, marketing, and consumer behavior. Keywords. Artificial Intelligence, Brand Authenticity, Brand Trustworthiness, Gen Z Consumer Perception, Social Media Marketing.
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2